2023
DOI: 10.1007/s12011-023-03616-0
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Nanoparticles Modulate Steroidogenesis-Related Genes and Improve Ovarian Functions via Regulating Androgen Receptors Expression in Polycystic Ovary Syndrome Rat Model

Abstract: Polycystic ovary syndrome (PCOS) occurs during the reproductive period in women and is characterized by reproductive, endocrine, and metabolic disorders. Androgen plays a decisive role in its pathogenesis due to the interaction between hyperandrogenism and insulin resistance, which might be improved by selenium nanoparticles (SeNPs). The present study aimed to clarify the effect of SeNPs on androgen synthesis and action in the PCOS model and the resulting effect on ovarian function. Fifty-five 7-week-old femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Moreover, our findings indicate that the ovarian endocrine components of TiO 2 -and TiO 2 /SA-treated animals are targets of NPs, as evidenced by the increase in abnormal (apoptosis and necrosis-like) morphologies of secretory cells, large atretic follicles, severe inflammatory cell infiltration, lymphocytosis, and vascular dilation and congestion (Figure 2C-F). The observed ovarian injuries with irregular cycles and significantly higher fractional contributions of ovaries in the TiO 2 and TiO 2 /SA groups could be associated with the structural damage of the mitochondria and nuclei of ovarian cells, including mitochondrial swelling, rupture, chromatin condensation, and irregularity in the nuclear membrane, as previously reported by Wang et al [48], but also with modifications in the expression of genes related to estrogen and progesterone synthesis and metabolism [49,50]. It was found that the application of TiO 2 NPs upregulated Cyp17a1, which is responsible for enhanced estradiol production [51], which is important considering that the expression levels of estradiol and progesterone, secreted by granulosa and luteal cells, are typically used to estimate ovarian endocrine function [52].…”
Section: Groupsupporting
confidence: 67%
“…Moreover, our findings indicate that the ovarian endocrine components of TiO 2 -and TiO 2 /SA-treated animals are targets of NPs, as evidenced by the increase in abnormal (apoptosis and necrosis-like) morphologies of secretory cells, large atretic follicles, severe inflammatory cell infiltration, lymphocytosis, and vascular dilation and congestion (Figure 2C-F). The observed ovarian injuries with irregular cycles and significantly higher fractional contributions of ovaries in the TiO 2 and TiO 2 /SA groups could be associated with the structural damage of the mitochondria and nuclei of ovarian cells, including mitochondrial swelling, rupture, chromatin condensation, and irregularity in the nuclear membrane, as previously reported by Wang et al [48], but also with modifications in the expression of genes related to estrogen and progesterone synthesis and metabolism [49,50]. It was found that the application of TiO 2 NPs upregulated Cyp17a1, which is responsible for enhanced estradiol production [51], which is important considering that the expression levels of estradiol and progesterone, secreted by granulosa and luteal cells, are typically used to estimate ovarian endocrine function [52].…”
Section: Groupsupporting
confidence: 67%
“…One study demonstrated that SeNPs reduce androgen production by downregulating the expression of key steroidogenic enzymes, including STAR, CYP11A1, CYP17A1, and HSD17B3, while increasing the expression of CYP19α1. Additionally, the block of AR expression was found ( 131 ). Fourteen days of low-dose SeNP supplementation normalizes the aberrant metabolic features of PCOS and inhibits the expression of inflammatory factors, including IL-6, TNF-α, and IL-1, via repairing the antioxidant KEAP1/NRF2 cascades ( 132 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%